Journal of Structural Biology - Journal of Structural Biology (Elsevier, 2026)
The Journal of Structural Biology (JSB) publishes papers dealing with the experimental structural analysis of biological material at every level of organization by all methods that lead to an understanding of biological function in terms of molecular and supramolecular structure. Advancements in computational and other structure analysis methods will also be considered by the journal.
FI 0.64
Q3
Keywords: Life Sciences; Cell & Molecular Biology; Ciencias de la vida; Biología celular; Biología molecular; Acuerdos transformativos; Transformative agreements; Función biológica